2022
DOI: 10.33492/jrs-d-21-00054
|View full text |Cite
|
Sign up to set email alerts
|

Organisational Safety Climate, Professional Driver Behaviours, and Crashes Among a Mixed Group of Professional Drivers

Abstract: The current study compared different driver groups and investigated the relationship between safety climate, driver behaviours, and crashes in a mixed group of professional drivers in Turkey. Two hundred and sixty drivers completed the scales developed explicitly for professional drivers, Transportation Companies’ Climate Scale and Occupational Driver Behaviour Questionnaire, along with the demographic form. Freight drivers scored higher on risky driver behaviours than passenger vehicle drivers. Organisational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Also, the measures used in the current study have demonstrated strong psychometric properties and criterion validity across a multitude of work settings (e.g. de Winter et al, 2015;Menendez et al, 2022;Yilmaz et al, 2022;Yousefi et al, 2016;Schüler & Matuszczyk, 2019;Moda et al, 2021).…”
Section: Strengths and Limitationsmentioning
confidence: 92%
“…Also, the measures used in the current study have demonstrated strong psychometric properties and criterion validity across a multitude of work settings (e.g. de Winter et al, 2015;Menendez et al, 2022;Yilmaz et al, 2022;Yousefi et al, 2016;Schüler & Matuszczyk, 2019;Moda et al, 2021).…”
Section: Strengths and Limitationsmentioning
confidence: 92%